2016
DOI: 10.1016/j.physc.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Current driven vortex-antivortex pair breaking and vortex explosion in the Bi2Te3/FeTe interfacial superconductor

Abstract: We investigated the dissipative regime of the Bi 2 Te 3 /FeTe topological insulatorchalcogenide interface superconductor at temperatures well below the Berezinski-Kosterlitz-Thouless transition. We observe a transition in the current-resistance and temperature-resistance curves that quantitatively agrees with the Likharev vortex-explosion phenomenon. In the limit of low temperatures and high current densities, we were able to demonstrate the regime of complete vortex-antivortex dissociation arising from curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, topological superconductivity (SC) has been theoretically predicted to be induced on the surface of TI-superconductor heterostructure via proximity effect, which may provide a platform to host non-Abelian Majorana fermions 5 . Interestingly, our group recently discovered a novel two-dimensional (2D) SC at the interface of two non-superconducting materials 6,7 , Fe1+yTe, a parent compound of iron-based superconductors, and Bi2Te3, a 3D TI, and later we reported further studies on this heterostructure such as the superconducting proximity effect 8 , current induced depairing 9 , anisotropic magnetic responses 10 and vortex dynamics 11,12 . Due to the complexity of this heterostructure, revealing the underlying mechanism of its induced 2D SC with a theoretical approach is very unlikely.…”
Section: Introductionmentioning
confidence: 93%
“…For example, topological superconductivity (SC) has been theoretically predicted to be induced on the surface of TI-superconductor heterostructure via proximity effect, which may provide a platform to host non-Abelian Majorana fermions 5 . Interestingly, our group recently discovered a novel two-dimensional (2D) SC at the interface of two non-superconducting materials 6,7 , Fe1+yTe, a parent compound of iron-based superconductors, and Bi2Te3, a 3D TI, and later we reported further studies on this heterostructure such as the superconducting proximity effect 8 , current induced depairing 9 , anisotropic magnetic responses 10 and vortex dynamics 11,12 . Due to the complexity of this heterostructure, revealing the underlying mechanism of its induced 2D SC with a theoretical approach is very unlikely.…”
Section: Introductionmentioning
confidence: 93%
“…Uppercritical-field measurements [41] and vortex-explosion measurements [45] showed that the superconductivity occurred within an interfacial layer of thickness d = 7 nm, which was much thinner than both the FeTe and Bi 2 Te 3 layers. Projection photolithography followed by argon-ion milling was used to pattern narrow microbridges optimized for the high current-density pulsed four-probe measurements.…”
Section: Samples and Experimental Informationmentioning
confidence: 99%